Synthesis and in vitro and in vivo characterization of highly β1-Selective β-Adrenoceptor partial agonists - Mistry, Shailesh N.; Baker, Jillian G.; Fischer, Peter M.; Hill, Stephen J.; Gardiner, Sheila M.; Kellam, Barrie (American Chemical Society, 2013)
β-Adrenoceptor antagonists boast a 50-year use for symptomatic control in numerous cardiovascular diseases. One might expect highly selective antagonists are available for the human β-adrenoceptor subtype involved in these diseases, yet few truly β1-selective molecules exist. To address this clinical need, we re-evaluated LK 204-545 (1),1 a selective β1-adrenoceptor antagonist, and discovered it possessed significant partial agonism. Removal of 1’s aromatic nitrile afforded 19, a ligand with similar β1-adrenoceptor selectivity and partial agonism (log KD of −7.75 and −5.15 as an antagonist of functional β1- and β2-mediated responses, respectively, and 34% of the maximal response of isoprenaline (β1)). In vitro β-adrenoceptor selectivity and partial agonism of 19 were mirrored in vivo. We designed analogues of 19 to improve affinity, selectivity, and partial agonism. Although partial agonism could not be fully attenuated, SAR suggests that an extended alkoxyalkoxy side chain, alongside substituents at the meta- or para-positions of the phenylurea, increases ligand affinity and β1- selectivity.